ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SETELAH PENUTUPAN GIANT PADA PT HERO SUPERMARKET TBK (HERO GRUP) - Kristiastuti, Francisca; Utari Kartika Sari; Nurul Abdilah Solehah (Accounting Research Journal, 2025)
Hero Group closed all Giant outlets in 2021. This was a effort by the company to reduce its burden and focus of business development on other sectors. This research was conducted to determine the difference in financial performance as a result of the closure of Giant outlets by comparing data from before and after the event. This study uses a comparative test, which is a test that compares two data. The test tool used is the paired sample t test. The data compared are the period before the closure of Giant in 2018 – 2020 and the period after the closure of Giant in 2021 – 2023. Based on the results there was no difference in PT Hero Supermarket, Tbk’s financial ratio as measured by current ratio, debt to equity ratio, and net profit margin both before and after the closure of Giant outlets. Meanwhile, the ratio of total assets turnover had a significant difference.